Fruit of the orchard : environmental justice in East Texas - Cromer-Campbell, Tammy, 1960- (University of North Texas Press, 2006)
In 1982, a toxic waste facility in the Piney Woods in Winona, Texas started causing cancer and birth defects in both humans and animals. Outraged by what she saw, Phyllis Glazer founded Mothers Organized to Stop Environmental Sins (MOSES) and worked tirelessly to publicize the problems in Winona. Here, she describes the history of Winona.